International Fragmentation: A Policy Perspective - Wilhelm Kohler (Johannes Kepler University of Linz, Department of Economics, 2000)
International fragmentation, or outsourcing, is often referred to as a distinctly novel feature in today's global economy. First observed in the US-Mexican context, the phenomenon is increasingly catching policy makers' attention also in Europe. As barriers between east and west are progressively removed, low wage countries in eastern Europe are likely outsourcing targets for western European firms. Against this background this paper provides a policy-oriented discussion of cross-border fragmentation. It starts with a precise definition of the phenomenon, putting it into the broader perspective of economic globalization. It then uses simple graphical tools to address, in a general way, several questions that appear relevant from western European point of view. Specifically, the paper idetifies conditions under which outsourcing is beneficial for a western country as a whole, and it highlights the internal redistributive effects associated with this gain. It then argues that preferential trading arrangements are formidable fragmentation barriers, particularly in Europe where a multiplicity of such arrangements has led to complex rules of origin. The efficiency loss from such barriers should provide a strong additional cause for a multilateral, as opposed to a regional, approach to trade liberalization.
Keywords: F11; F13; F19; 330; Globalisierung; Outsourcing; Welt